Effect of temperature on exercise metabolism, hypoxia tolerance, and RNA-seq analysis in Sinilabeo rendahli from the Yangtze River, China - Li, Sheng; Guo, Hui; Du, Chun-Ying; Tao, Yi-Xi; Feng, Jing-Yun; Xu, Hao; Pang, Xu; Li, Yun (Frontiers in Ecology and Evolution, 2023)
Temperature variation affects the growth, maturation, and distribution of fish species due to increasing constraints on physiological functions. It is of theoretical and practical importance to study the adaptability of fish to temperature change. We experimentally investigated the routine metabolic rate (RMR), individual metabolic rate (MO2), temperature quotient (Q10), loss of equilibrium (LOE), and critical oxygen tension (Pcrit) after 14 days of acclimation in Sinilabeo rendahli (Teleostei, Cypriniformes, Labeoninae), an endemic fish of the Yangtze River in China, at three temperatures (15, 20 and 25 °C). Meanwhile, we sampled muscle tissue from juvenile S. rendahli under experimental conditions after 28 days and performed transcriptome RNA sequencing (RNA-seq). As expected, the Pcrit of the fish at the above acclimation temperatures were determined to be 1.07, 1.28, and 1.33 mg L-1, respectively, and corresponded with increasing acclimation temperatures (15-25 °C). RMR was positively correlated with Pcrit (r = 0.4711, p = 0.0201), negatively correlated with LOE (r = -0.4284, p = 0.0367), and significantly positively correlated with MRcrit (r = 0.8797, p < 0.001) at temperatures ranging from 15 to 25 °C. In addition, a total of 4710 differentially expressed genes (DEGs) were identified. The results of DEGs analysis and KEGG clustering analysis indicated that energy metabolism played a central role in thermal stress in S. rendahli for the major upregulated genes. This was followed by autophagy, mitophagy, cardiac muscle contraction, extracellular matrix (ECM)-receptor interaction, and protein digestion and absorption. This study is significant for understanding the adaptive response of S. rendahli to thermal stress. Even more importantly, this study shows that S. rendahli is more suitable for cold water life.